An investigation into the impact of particle properties on flow behaviors - Zhao, Ya (Nanyang Technological University, 2020)
The particulate system is very common in nature and in industry. The studies on the flow behaviors in the hopper and horizontal pneumatic conveying, which are quite common equipment to process the particles in application reveal the complicated dynamic behaviors due to the interactions between the individual particles and the interactions with surrounding gas and wall. The recent development in computational the motion and effect of a large number of small particles codes and computing capabilities enable detailed study of interactions between the particle and the wall and inter-particles, hence advancing mechanistic understanding of the particle dynamic behaviors. The impact of particle properties (i.e., particle polydispersity, particle size, particle shape, particle density, and friction coefficient) on the discharge characteristics (i.e., discharge rate, particle velocity, segregation, packing, collision force) are studied. Analysis of hopper flow with spherical particles of lognormal particle size distributions (PSDs) (Chapter 3 – 5) showed (i) the hopper discharge rate decreases with the increase of PSD width and the fluctuations of the discharge rate increase as the PSD width, which is correlated to the performance of particle velocity, particle angular velocity, and the collision force. However, the well-known Beverloo correlation predicts the discharge rates of lognormal PSDs poorly; (ii) the size-segregation increases as PSD width increases; (iii) To reduce the jamming probability, the PSDs width (σ/μ), the friction coefficient, and the initial fill height can be reduced, but not changes with the particle density. The study of hopper flow with non-spherical particles (Chapter 6 and 7) revealed: (i) For the monodisperse systems, particle shape is the dominant factor dictating discharge rate, compared to other factors like aspect ratio, preferential orientation and packing; (ii) Regarding the binary-size mixtures, while the discharge rates are still dictated by particle shape, the positive correlation between discharge rate and solid volume fraction or mean aspect ratio is clear; (iii) As for the binary-shape mixtures, the discharge rates are similar for all twelve mixtures, reflecting a surprising lack of shape effects, which in turn means the negligible impact of solid volume fraction, aspect ratio and segregation extent; (iv) In the lognormal PSDs systems, the discharge rates decrease and further jamming as PSD width (σ/μ) increases and the particle angularities increases. The packing of the hopper is associated with the PSD width and shape of the particles. Finally, the influences of initial particle charge on the minimum pickup velocity in the pneumatic conveying are evaluated (Chapter 8). The experimental results found (i) for the particle initial charge range investigated (-10 to 10 nC), Upu increased monotonically with particle initial charge; (ii) the well-acknowledged correlation mis-predicted Upu by up to 10% for monodisperse systems and up to 40% of binary-size systems. This underscores the necessity to account for particle initial charge in such correlations, particularly for polydisperse particle systems.